2006
DOI: 10.1080/02791072.2006.10400603
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use and Adverse Consequences in the Rural Southern United States: An Ethnographic Overview

Abstract: Research on methamphetamine use and related issues often uses data from in-treatment and post-treatment populations in urban areas. Rural ethnographic studies are less common. particularly self assessments by active methamphetamine users that explore use patterns and their adverse consequences. Such work is especially rare in the rural South. where illicit methamphetamine manufacture and use have recently been increasing. This article presents an ethnographic overview of methamphetamine use in rural Kentucky a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…Murphy and colleagues (2014) found meth use significantly increases toothaches and embarrassment due to the alteration of physical appearance resulting from missing teeth, and communities with higher levels of crystal meth users also tend to have more dental health problems in their offending populations (Brunswick, 2005;Sexton, Carlson, Leukefeld, & Booth, 2006). Moreover, the grizzly images of ''meth mouth'' emanating from the nationally recognized antimethamphetamine media campaign ''Faces of Meth'' has inscribed the stigma associated with drug use and imprisonment into the popular consciousness (Linnemann & Wall, 2013), ''with profound consequences for enshrining teeth as a primary physical marker of class status'' (Murakawa, 2011, p. 224).…”
mentioning
confidence: 99%
“…Murphy and colleagues (2014) found meth use significantly increases toothaches and embarrassment due to the alteration of physical appearance resulting from missing teeth, and communities with higher levels of crystal meth users also tend to have more dental health problems in their offending populations (Brunswick, 2005;Sexton, Carlson, Leukefeld, & Booth, 2006). Moreover, the grizzly images of ''meth mouth'' emanating from the nationally recognized antimethamphetamine media campaign ''Faces of Meth'' has inscribed the stigma associated with drug use and imprisonment into the popular consciousness (Linnemann & Wall, 2013), ''with profound consequences for enshrining teeth as a primary physical marker of class status'' (Murakawa, 2011, p. 224).…”
mentioning
confidence: 99%
“…Most of the prior research on methamphetamine use has been conducted among urban populations in western states. As Sexton and colleagues (2006) noted, in the rural communities of Kentucky and Arkansas, small-scale, independent methamphetamine production has contributed to the development of a flexible, localized drug economy with private distribution channels, close social relationships and often noncommercial, drug sharing behaviors. The rural methamphetamine economy differs in many ways from crack scenes, which have been frequently portrayed as highly competitive arenas where most social connections are based on greediness and hostility and even intimate relationships are reduced to commodities to be exchanged for crack (Daniulaityte, Carlson, & Siegal 2007; Bourgois & Dunlap 1993; Inciardi, Lockwood, & Pottieger 1993; Ratner 1993; Carlson & Siegal 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed between methamphetamine and cocaine (crack, in particular) associations with depressive symptoms should be considered in the context of prior studies showing that some individuals use methamphetamine to enhance productivity, energy, and daily functioning in their roles as family caregivers and providers (Daniulaityte, Carlson & Kenne 2007; Sexton et al 2006; Morgan & Beck 1997). One study found that methamphetamine users spent less money on drugs and were more successful at participating in “normal” activities of daily life than cocaine users (Simon et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Their findings support the hypothesis that meth users may be more likely than other drug users to commit acts of violence. Sexton, Carlson, Leukefeld, and Booth (2008), Sexton et al (2005), and Sexton et al (2006) have looked at patterns of meth use and production in the rural South through longitudinal ethnographic interviews with small numbers of users. Listwan, Shaffer, and Hartman examined meth treatment in drug courts (2008), and found that drug of choice does not influence drug court outcomes.…”
Section: Goldstein and The Drug-crime Nexusmentioning
confidence: 99%